A wheeled robot to monitor grape growth. (Research'eu results magazine)
Just like great wine needs time, great grapes require continuous attention and reliable assessment tools. Noting the absence of a convincing alternative to manual sampling and analysis, an EU-funded consortium has developed VineRobot, an 'Unmanned ground vehicle' (UGV) equipped with non-invasive sensor technology.